2020
DOI: 10.21203/rs.3.rs-22464/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus-2 and Pulmonary Tuberculosis Coinfection: Double Trouble

Abstract: The ongoing pandemic of novel coronavirus Severe Acute Respiratory Syndrome Coronavirus - 2 (SARS-CoV-2) has received worldwide attention by becoming a major global health threat. We encountered one case of SARS-CoV-2 and pulmonary tuberculosis (TB) coinfection which has not been frequently reported. A 76 year old female presented with acute respiratory symptoms superimposed on chronic symptoms, suggestive to have pneumonia. Oropharyngeal throat swab sample for SARS-CoV-2 infection was positive as detected by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIVpositive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This needs careful interpretation due to a wide overall 95% CI as well as due to studies with different designs. This evidence is supported by two large cohort studies conducted in Spain and South Africa, showing that the risks for PCR-con rmed COVID-19 diagnosis, hospitalization, Intensive Care Unit (ICU) admission, and death among HIVpositive persons receiving ART were greater in men compared to old age [42][43][44][45][46][47][48]. However, the risk for hospitalization varied by the nucleoside transcriptase inhibitor (NRTI) regimen and was lower in patients receiving TDF/FTC versus those receiving other regimens [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 88%
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each article that met selection criteria was fundamentally assessed for Author/Country, Population/Study design, Exposures, Comparators, Treatments, TB occurrence and SARS/MERS/COVID-19 severity, recovery and mortality rate. [28][29][30][31], one case control study [32] and four case series [33][34][35][36] were conducted in China, two case series [37][38] were done in Singapore, one case series [39] and one case control study [40] were undertaken in Saudi Arabia, a case series [41] was conducted in Italy, one cohort study was done in South Africa [42] and another in the Philippines [43], one case study was conducted in the United State of America [44], other three case studies were found in Turkey [45], Hong Kong [46] and India [47] respectively. Lastly, a retrospective cohort was undertaken in eight countries (Italy, Belgium, Brazil, France, Russia, Singapore, Spain, and Switzerland) [27].…”
Section: Search Resultsmentioning
confidence: 99%